(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article discisses the factors that infuenced the formation of text of reasoning of monothematic type and it’s specific modifications. The essays of the second half of the XVII century being examined, as an intermediate genre that occurs at the intersection of literature, journalism and philosophy. This period is characterized by the formation of English literature national language norms, when philosophical, lyrical, emotional, intellectual understanding of life changes took place and the battle in the literature over the new style, designed to reflect the dynamics of the inner life of man has begun. Being investigated the stylistic influence and sings of the new style in connection with principal literary direction of epoch – classicism. Attention is drawn to rational-logical direction of the style. Special attention is paid to small epic forms (essays, meditations, diaries), specific language which is dictated by the general structural pecularities of this prose, strictly rational-logically and rhetorically organized. The reference to the analysis of the texts of the second half of the XVII century is not accidental. This period was defined by researchers as “experimental” in the development of modern English prose. The variety of later developed verbal forms of prose was most vigorously pioneered precisely in that century. The text of reasoning is considered as a whole-formed, structural and communicative unity created on the basis of the compositional-speech form, the elements of which reproduce the speech process as the process of the work of consciousness. The revival of rhetoric in the XVII century also determined the special nature of the generation of texts in which lexico-semantic and synthetic levels were subjected to compulsory organization. The element of consciousness and correctness is obvious here, so the structure appears naked. The reasoning here is not contaminated with other compositional-speech forms, but represents the whole speech production. The basis for the proposed classification of English prose texts of second half of the XVII century is not genre-based features, but a type of compositional-speech form. The typological features of the speech structure of text-reasoning are studied. The composition of the argumentative texts of the “hard” and ”non-rigid” type-their lexical-syntatic and stylisic features is studied. The specificity of the linguistic organization of the cyclical type of reasoning is also considered.